GLOBAL INJUSTICE AND INEQUALITY: REFLECTIONS ON WHY CITIZENSHIP EDUCATION MATTERS - Riana Tambunan; Ahmad Rizaldi; Aulia Riski (Universitas Negeri Medan, 2023)
Global injustice and inequality are problems related to the unequal distribution of resources and opportunities throughout the world. This causes a large number of people and countries to have limitations in achieving their potential. Therefore, it is necessary to prepare prospective citizens who are ready to face changes in the order of life in the country. Education is expected to be able to overcome the country's problems, especially injustice, and inequality. In building global insight and forming good global citizens, there are basic values contained in civic education. This value is the goal and foundation for the development of civics education. By using qualitative research methods through literature studies, the authors try to examine how important the role of civics education is in addressing global injustice and inequality. This research was conducted through several stages including collecting library data, taking notes, reviewing data sources, and processing information. The conclusion from this study is that it is important to involve the integration of civics education in the education system, focus on practical skills, community participation, research and innovation support, and building international alliances. Civic education also helps build a culture of tolerance and reinforces values of social solidarity to help eradicate discrimination and promote equality.